REVITALISASI MONUMEN PERS SEBAGAI SALAH SATU CAGAR BUDAYA DI SURAKARTA - Sholeh, Restu Mohammad (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2015)
The purpose of this study are to describe: (1) To know the history of the development of the press in Surakarta, (2) To know the process of the implementation of the National Press Monument revitalization of cultural heritage objects, (3) To determine the changes in the revitalization of cultural heritage objects.This form of qualitative descriptive research, which is a way of examining an event in the present to generate descriptive data in the form of words written or spoken of certain people or behaviors that can be observed by using certain steps.This study used a single fixed strategy case study. Source of data used are the source of objects, places, events, informants, and documents. Data collection techniques used are observation, interviews, and document analysis. The sampling technique used are purposive and snowball sampling.This study, to look for the validity of the data used two techniques, namely triangulation of data and methods. The data analysis technique used is interactive analysis, namely the analysis process that moves between the three components which include data reduction, data presentation, and verification / conclusion.Based on these results it can be concluded: (1) Early history of the press in Surakarta Bromartani marked by the birth of the magazine when it was reckoned to be the pioneer of the development of the local press in Indonesia. Politically, in the process of publishing a newspaper in Surakarta is free. This situation is marked by the Dutch colonial politics in 1854 were relatively very loose in the Indonesian newspaper publishing. (2) One aspect that is often overlooked in development activities is to revitalize historic buildings. Attention is always glued to the new buildings are more impressive as a means of modernity in the region / area specific. As a result, many old buildings were dismantled or demolished even abolish / eliminate them. (3) The results and impact of the revitalization process Monument National Press as the Surakarta cultural heritage reveals its true face. The building that formerly less well maintained, is now starting to look clean and well maintained.